The Effect of Disclosing Sustainability Reports with the Global Reporting Initiative (GRI) G4 and Green Accounting on the Value of Mining Companies on the IDX in 2020-2023 - Susilowati Syakur; Khomsiyah Khomsiyah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to investigate the impact that the publication of sustainability reports through the Global Reporting Initiative G4 and green accounting have on the market value of mining firms listed on the Indonesia Stock Exchange (BEI). This study takes a quantitative approach to its investigation. During the year of 2020-2023, the population is comprised of 47 mining businesses that are listed on the Baltic Exchange. The sample includes 26 mining companies. The dependent variable in this study is Market Value, while the independent variables are Sustainability Report Disclosure and Green Accounting. The research utilizes secondary data from annual reports spanning from 2020 to 2023. The analytical technique employed is multiple linear regression. The conclusions drawn from this research are: 1) Sustainability Report Disclosure has a significant and positive impact on Market Value, and 2) Green Accounting has a significant and positive impact on Market Value. Recommendations based on the findings are: 1) Future research should include a broader range of company sectors to avoid limitations to only sanctioned and non-sanctioned companies, and 2) Future studies could employ alternative analytical methods to obtain differing research outcomes.